News and myth – dengue fever - Tan, Ser Han (2016)
This project sets out to explore the possibilities of leveraging technology to assist in dengue prevention as well as increase awareness of the uninformed public of the dangers of mosquitoes, the diseases they transmit and news of outbreaks.